Validating the PANDORA GenAI Susceptibility Rubric for Higher Education Assessment: A Field Test of All Translation and Interpreting BA Assignments - Brufau Alvira, Nuria; Bannister, Peter; Santamaría Urbieta, Alexandra (Higher Education Quarterly, 2026)
This study, conducted at a fully online Spanish higher education institution, documents the validation of a bespoke quality as-sessment tool designed to measure the susceptibility of formative assignments to AI academic misconduct. The research exploredthe impact of Generative AI (GenAI) technologies in the Humanities. The framework study consisted of four stages: the designof a rubric (Stages 1–3) and its large-scale validation (Stage 4) through a field test in the Translation and Interpreting StudiesBachelor's Degree. This paper presents stage 4 results where lecturers (n = 29), using a bottom-up approach, voluntarily appliedthe tool to their teaching contexts and analysed assignments (n = 151) using the rubric, revealing significant vulnerabilities inassessments easily converted by GenAI or lacking originality and collaboration. The findings guided AI-integrated assessmentdesigns that encourage complexity, creativity, and ethical engagement. This study outlines effective GenAI practices in assess-ment design and emphasises innovative methods for academic integrity in higher education.
Keywords: AI; assessment; higher education; institutional regulation development; rubric